OXIDATIVE STRESS IN BRAINS OF MALE RATS INTOXICATED WITH ALUMINIUM AND NEUROMODULATING EFFECT OF CELASTRUS PANICULATUS ALCOHOLIC SEED EXTRACT. - Sumathi, Thangarajan; Shobana, Chandrasekar; Mahalakshmi, Varadharajan; Sureka, Ramachandran; Subathra, Manogaran; Vishali, Arunachalam; Rekha, Krishnamoorthi (Asian Journal of Pharmaceutical and Clinical Research, 2013)
The objective of the present study was to investigate whether the alcoholic seed extract of Celastrus paniculatus (ASECP) could potentially prevent aluminium induced neurotoxicity in the cerebral cortex, hippocampus and cerebellum of the rat brain. Male albino rats were administered with AlCl3 at a dose of 4.2mg/kg/day i.p. for 4 weeks. Experimental rats were given Celastrus paniculatus seed extract in two different doses of 200mg and 400mg/kg/day orally 1hr prior to the AlCl3 administration for 4 weeks. At the end of the experiments, aluminium administration significantly decreased the level of GSH and the activities of SOD, CAT, GPx, GR, Na+/K+ ATPase, Ca2+ ATPase and Mg2+ ATPase and increased the level of LPO and the activities of ALP, ACP, ALT and AST in all the brain regions when compared with control rats. Pre-treatment with ASECP at a dose of 200mg/kg b.w increased the antioxidant status and activities of membrane bound enzymes and also decreased the level of LPO and the activities of marker enzymes significantly, when compared with aluminium induced rats. Al treatment also revealed an increase in DNA fragmentation as evidenced by an increase in number of comets. Interestingly, ASECP pretreatment reduced the damage inflicted on DNA by aluminium. Aluminium induction also caused histopathological changes in the cerebral cortex, cerebellum and hippocampus of rat brain which was reverted by pretreatment with ASECP. The present study clearly indicates the potential of seed extract of Celastrus paniculatus in counteracting the damage inflicted by Al on rat brain regions.